2008
DOI: 10.1099/mic.0.2008/018085-0
|View full text |Cite
|
Sign up to set email alerts
|

d-Lactate metabolism and the obligate requirement for CO2 during growth on nitrite by the facultative lithoautotroph Nitrobacter hamburgensis

Abstract: Nitrobacter hamburgensis X14 is a facultative lithoautotroph that conserves energy from the oxidation of nitrite (NO À 2 ) and fixes carbon dioxide (CO 2 ) as its sole source of carbon. The availability of the N. hamburgensis X14 genome sequence initiated a re-examination of its mixotrophic and organotrophic potential, as genes encoding three flavin-dependent oxidases were identified that may function to oxidize lactate, providing energy and carbon for growth. The response of N. hamburgensis to D-and L-lactate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…It is possible that some NOB tended to use the simple organic carbon from the organic fertilizer or the organic products decomposed by fungi. Previous studies have shown that facultative/mixotrophic NOB were found to assimilate a narrow range of simple organic carbon compounds (e.g., acetate, D -lactate, pyruvate and glycerol) ( Bock, 1976 ; Starkenburg et al, 2008 ). Fertilizer-induced shifts in nitrifier community composition may be explained by the direct/indirect effects of selective feeding on certain nutrient substance types as a result of the general effect of fertilizer on environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some NOB tended to use the simple organic carbon from the organic fertilizer or the organic products decomposed by fungi. Previous studies have shown that facultative/mixotrophic NOB were found to assimilate a narrow range of simple organic carbon compounds (e.g., acetate, D -lactate, pyruvate and glycerol) ( Bock, 1976 ; Starkenburg et al, 2008 ). Fertilizer-induced shifts in nitrifier community composition may be explained by the direct/indirect effects of selective feeding on certain nutrient substance types as a result of the general effect of fertilizer on environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The growth rate of N. europaea under such conditions was lower than the growth rate on CO 2 , but a high growth yield was observed (17). Enhanced growth yield and rate have also been reported for Nitrobacter hamburgensis (NOB) when D-lactate and NO 2 Ϫ were supplied as the sole carbon source and as energy source, respectively (52). Similarly, Nitrospira appeared to simultaneously assimilate inorganic and organic carbon (e.g., pyruvate), but it is still unclear whether Nitrospira spp.…”
mentioning
confidence: 89%
“…A likely explanation for this discrepancy is that the AOB were utilizing organic compounds as a carbon source in the low-DO systems, decreasing the need for an energetically expensive reductive process to convert CO 2 to cellular carbon inherent in autotrophic metabolism. In contrast, mixotrophic metabolism reduces the energy requirement for cell synthesis as organic carbon is used, thereby increasing the cell yield (17,43,52,62). Chemolithoorganotrophic growth of AOB has been demonstrated under anoxic conditions where molecular oxygen is replaced with nitrogen dioxide or nitrogen tetroxide as electron acceptor and pyruvate or lactate is replaced with CO 2 as carbon source (24,48).…”
Section: Vol 77 2011 High Yield Of Aob In Low-do Systems 7791mentioning
confidence: 99%
“…The Nitrobacter hamburgensis X14 strain oxidizes nitrite to conserve energy and is commonly used in nitrification research [8]. Although the strain was isolated more than 100 years ago [9], limited research on this strain has been published due to the lack of genetic manipulation tools.…”
Section: Introductionmentioning
confidence: 99%